2020
DOI: 10.1093/mnras/staa3644
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mechanism for the decomposition of CH3NH2 and implications to interstellar glycine

Abstract: Complex organic molecules from extraterrestrial source are expected to have contributed to the Early Earth chemistry. Methylamine (CH3NH2) has already been observed in the interstellar medium (ISM) and is generally related to the formation of glycine, although the latter has not been identified in the ISM yet. In this work, a chemical model for CH3NH2 was investigated, comprising twenty-eight reactions and including reactions involving NH3 and HOOC, aiming to understand the main routes for formation and decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Sato et al employed state-of-the-art DFT calculations and reported that reaction (1) is the most feasible route 7 ; these authors proposed that the aminomethyl radical, •CH 2 NH 2 , might be produced from successive hydrogenation of HCN or H abstraction from CH 3 NH 2 by •OH or •NH 2 5 9 . A similar theoretical chemical model involving NH 3 and •HOCO was also proposed to understand the main routes for the formation and decomposition of CH 3 NH 2 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Sato et al employed state-of-the-art DFT calculations and reported that reaction (1) is the most feasible route 7 ; these authors proposed that the aminomethyl radical, •CH 2 NH 2 , might be produced from successive hydrogenation of HCN or H abstraction from CH 3 NH 2 by •OH or •NH 2 5 9 . A similar theoretical chemical model involving NH 3 and •HOCO was also proposed to understand the main routes for the formation and decomposition of CH 3 NH 2 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Next, let us consider the relationship between reactive orbitals and reaction pathways by exploring the reactive orbitals for as comprehensive reaction paths as possible from the equilibrium structure of glycine molecule. Note that more reaction paths of very similar conformers 52 and very high-energy isomers 53 are suggested, though the presence of these paths is supposed to depend on the level of the calculation method used. Figure 4 displays the generated reaction pathways from glycine molecule with the corresponding reactive orbital pairs.…”
Section: Global Reaction Route Map Of Formaldehydementioning
confidence: 99%
“…[ 29 ] Actually, MA is also an important interstellar chemical found several decades ago. [ 30,31 ] Owing to the reasons, gas/liquid chromatography, [ 32 ] electrochemical methods, [ 33,34 ] and quartz crystal microbalance (QCM), [ 35 ] etc., have been developed for the sensitive detection of MA in the air. The methods, however, are difficult to apply to on‐site and rapid detection due to tedious operation and equipment reasons.…”
Section: Introductionmentioning
confidence: 99%